A general approach to S-rhodamines from diaryl thioethers and their application in constructing pH probes. Issue 29 (12th July 2022) - Sun, Dongsheng; Yang, Shixu; Ma, Junxia; Liu, Can; Sun, Jiabing; Li, Yulong; Deng, Fei
Abstract : A general strategy for the efficient preparation of S-rhodamines from the condensation of diaryl thioether and 2-carboxybenzaldehydes. Abstract : A general strategy for the efficient preparation of S-rhodamines from the condensation of diaryl thioether and 2-carboxybenzaldehydes was reported. We further took a morpholine containing spirolactam structure as an example to illustrate that these S-rhodamine dyes could be utilized to construct fluorescent probes based on the ring-opening process. This work provided a general approach for the synthesis of novel S-rhodamine dyes, thus possibly facilitating the development of fluorescence imaging.